2020
DOI: 10.1002/lio2.431
|View full text |Cite
|
Sign up to set email alerts
|

A new landmark for the identification of the facial nerve during parotid surgery: A cadaver study

Abstract: Objective Precise knowledge of facial nerve anatomy is crucial for parotid surgery. Although several surgical landmarks to identify the facial nerve have been described in literature, their position is variable, inconsistent, and difficult to follow in some cases. The purpose of this study was to prove that the facial nerve trunk (FNT) is located midway between the mastoid tip (MT) and osteocartilaginous junction of the external auditory canal (EAC). Methods A prospective study of 7 frozen cadaver specimens, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These include the identification of stylomastoid foramen, posterior belly of the digastric muscle, tragal pointer, mastoid process, tympano-mastoid suture and identification of peripheral branches of the facial nerve. Al-Qahtani et al, after cadaveric dissection, have recently confirmed the consistent location of the facial nerve truck at the midpoint between the mastoid tip inferiorly and the osteocartilaginous junction of the external auditory canal superiorly 12,14 . As the evidence does not superior antegrade to retrograde dissection and where anatomical identification is the primary approach, it is also advised to limit the exploration of the facial nerve to the branches in close relation with the adenoma 15,16 .…”
Section: Discussionmentioning
confidence: 82%
“…These include the identification of stylomastoid foramen, posterior belly of the digastric muscle, tragal pointer, mastoid process, tympano-mastoid suture and identification of peripheral branches of the facial nerve. Al-Qahtani et al, after cadaveric dissection, have recently confirmed the consistent location of the facial nerve truck at the midpoint between the mastoid tip inferiorly and the osteocartilaginous junction of the external auditory canal superiorly 12,14 . As the evidence does not superior antegrade to retrograde dissection and where anatomical identification is the primary approach, it is also advised to limit the exploration of the facial nerve to the branches in close relation with the adenoma 15,16 .…”
Section: Discussionmentioning
confidence: 82%
“…Parotid surgery is warranted for benign and malignant neoplasm, chronic inflammatory diseases, sialolithiasis, intra-parotid cysts/sinuses and lymphadenopathy, and many other diseases. The methods of identification of the facial nerve and its importance are aptly described by many eminent surgeons using various anatomical landmarks during parotidectomy [4]. In this article styloid process is considered the very consistent robust anatomical landmark in the triangle technique in conjunction with the tragal cartilage to tragal pointer and the origin of the posterior belly of the digastric muscle at the mastoid tip.…”
Section: Introductionmentioning
confidence: 99%
“…20,26 Many researches have been widely investigated the distance of the anatomical landmarks to the facial nerve trunk (Table 1)(Figure 20). 4,67,[70][71][72][73][74][75][76][77] Figure 20 Distance of the temporal branch of the facial nerve correlated to the external auditory. [70][71][72] Table 1 The distance of the facial nerve trunk to the anatomical landmarks.…”
Section: The Facial Nerve Trunk and Its Branchesmentioning
confidence: 99%
“…[70][71][72] Table 1 The distance of the facial nerve trunk to the anatomical landmarks. Al-Qahtani et al 77 (2020)…”
Section: The Facial Nerve Trunk and Its Branchesmentioning
confidence: 99%
See 1 more Smart Citation